2011
DOI: 10.1542/peds.2010-0939
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Crossover Study of Automated Control of Inspired Oxygen in Ventilated Preterm Infants

Abstract: In infants with fluctuations in Spo(2), automated Fio(2) adjustment improved maintenance of the intended Spo(2) range led to reduced time with high Spo(2) and more-frequent episodes with Spo(2) between 80% and 86%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
143
13

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(169 citation statements)
references
References 16 publications
13
143
13
Order By: Relevance
“…In a clinical setting, meeting SpO 2 target ranges depends-among others-on patient-caretaker ratio (31). Most closed loop studies compared automated to routine clinical care (14,21,(24)(25)(26), only one study could show a significant improvement comparing closed loop to dedicated manual control (22). In addition, in our study, alarm range was equal to target range, which created an ideal setting for dedicated manual control as caregivers are more effective in keeping SpO 2 within alarm limits then within target limits in preterm infants (32).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a clinical setting, meeting SpO 2 target ranges depends-among others-on patient-caretaker ratio (31). Most closed loop studies compared automated to routine clinical care (14,21,(24)(25)(26), only one study could show a significant improvement comparing closed loop to dedicated manual control (22). In addition, in our study, alarm range was equal to target range, which created an ideal setting for dedicated manual control as caregivers are more effective in keeping SpO 2 within alarm limits then within target limits in preterm infants (32).…”
Section: Discussionmentioning
confidence: 99%
“…A promising solution to optimize oxygen therapy is the employment of an automatic "closed loop" system for regulation of FiO 2 based on SpO 2 . Several clinical trials with different devices have proven feasibility of automated closed loop FiO 2 control in the NICU for various modes of ventilation, mixed populations, and by using different algorithms (14,(21)(22)(23)(24)(25)(26). In addition, an overall reduction of manual interventions during automated control was found in these studies, indicating facilitation of caretakers and nursing staff in clinical routine (27,28).…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…All studies except one were conducted in high‐income settings. These studies showed that, with manual titration, SpO 2 was outside and/or above the target range 18–84% and 15–58% of time, respectively 15, 16, 17, 18, 19, 20, 21, 22, 25, 26. In Colombia, SpO 2 was within or above the target 34 and 55% of the time, respectively 21.…”
mentioning
confidence: 98%